Implementasi Big Data Analytics Dalam Meminimalisir Fraud - Herlinia, Sella; Lidyah, Rika (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
The high number of fraud cases that occur in Indonesia has caused large amounts of losses to be suffered by the country. Thus, finding effective methods to detect fraud is still the focus of many parties, especially the Government. Therefore this research was carried out. This research aims to analyze the implementation of big data to minimize froud. This research uses the Literature Review method. Contains reviews, summaries and the author's opinion about several sources in the library, the results obtained from this research were collected from previous research, the use of big data